Evaluation of the anticoagulant potential of polysaccharide-rich fractions extracted from macroalgae*. Issue 18 (17th September 2017) - Adrien, Amandine; Dufour, Delphine; Baudouin, Stanislas; Maugard, Thierry; Bridiau, Nicolas
Abstract: The aim of this study was to evaluate the potential anticoagulant activity of sulphated polysaccharide-containing extracts of six french edible marine macroalgae. Aqueous extracts of brown ( Himanthalia elongata, Laminaria digitata, Ascophyllum nodosum, Fucus vesiculosus ), green ( Ulva lactuca ) and red ( Chondrus crispus ) macroalgae were prepared and their biochemical properties were determined, including major biomolecules, sulphate and ash contents. The anticoagulant activity of each extract was investigated using different scales from the specific antithrombin-dependent pathway (anti-Xa and anti-IIa) to the intrinsic and/or common (Activated Partial Thromboplastin Time, APTT), extrinsic (Prothrombin Time, PT) or common (Thrombin Time, TT) anticoagulant pathways, and compared with those of commercial anticoagulants, heparin and Lovenox®. Laminaria digitata, Fucus vesiculosus and Chondrus crispus extracts showed a significant APTT anticoagulant capacity, only 5-fold lower than that of Lovenox®, which is a pure low molecular weight heparin used as an anticoagulant agent to prevent pulmonary embolism in patients undergoing surgery. Abstract :